The Role Of Intellectual Capital In Modernizing The Influence Of Good Corporate Governance And Sharia Compliance Of Sharia Banks - Iva Nur Azizah; Yayu Putri Senjani (Universitas Islam Negeri (UIN) Walisongo Semarang, 2019)
Purpose - Improved financial performance of Islamic banks can be done by improving the system of corporate governance and sharia compliance. In addition to a good corporate governance system and sharia compliance, other factors such as intellectual capital in sharia banks can also improve financial performance. The purpose of this study was to determine the role of intellectual capital in moderating the effect of good corporate governance and sharia compliance on financial performance of sharia banks in 2013-2017.Method - Sampling technique used is purposive sampling. The analytical technique used is panel data regression test with software Eviews 9.Result - It is found that good corporate governance and Islamic Income Ratio have an effect on the financial performance of sharia banks which is poxied by return on assets. Besides that, intellectual capital modernizesgood corporate governance and Islamic Income Ratio on the financial performance of sharia banks, but it does not modernize sharia compliance which is proxied with Profit Sharing Ratio (PSR) and Zakat Performing Ratio (ZPR).Implication - This study uses the data from 14 islamic commercial banks in Indonesia.Originality - The papers look into the role of intellectual capital variables in the relationship of good corporate governance and sharia compliance to the financial performance.